STUDENTS’ MOTIVATION ON ONLINE LEARNING DURING COVID-19 AT SENIOR HIGH SCHOOL IN SIBERUT SELATAN - Adela Maharani Putri; M. Khairi Ikhsan; Hevriani Sevrika (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2022)
Abstract The purpose of this study was to find out how the motivation of students at SMA N 1 Siberut Selatan in learning online during the pandemic. This study uses a qualitative method. The data collection technique used is total sampling. The participants in this study were twenty-four students from class XI IIS. The instrument of this research is to distribute a questionnaire (questionnaire), interview and also record voice (interview). Collecting data by distributing questionnaires to twenty-four students and interviewing five students. Researchers used intrinsic and extrinsic motivation as data sources and used a questionnaire in collecting data and interviews as data reinforcement. Based on data analysis, the researcher concluded that the motivation of students in class XI of SMA N 1 Siberut Selatan towards online learning was high. Keywords: Student Motivation, Online Learning.Abstrak Tujuan dari penelitian ini adalah untuk mengetahui bagaimana motivasi siswa di SMA N 1 Siberut Selatan dalam belajar online di masa pandemi. Penelitian ini menggunakan metode kualitatif. Teknik pengambilan data yang digunakan adalah total sampling. Partisipan dalam penelitian ini sebanyak dua puluh empat siswa dari kelas XI IIS. Instrumen penelitian ini adalah dengan menyebarkan angket (questionnaire), mewawancarai dan juga merekam suara (interview). Pengumpulan data dengan cara membagikan questionnaire ke dua puluh empat siswa dan mewawancarai lima siswa. Peneliti menggunakan Intrinsic dan Ekstrinsik motivasi sebagai sumber data serta menggunakan questionnaire dalam mengumpulkan data dan interview sebagai penguat data. Berdasarkan analisis data, peneliti menyimpulkan bahwa motivasi siswa di kelas XI SMA N 1 Siberut Selatan terhadap pembelajaran online, tinggi. Kata Kunci : Motivasi Siswa, Pembelajaran Online